PENGATURAN DAN PENERAPAN SISTEM PEMBIAYAAN MURABAHAH DI BANK PERKREDITAN RAKYAT SYARIAH - Bayu Sendy Pratama; Sukarmi Sukarmi (Jurnal Akta, 2017)
The most developed sharia bank financing system, because the financing systems is considered the most fair and far from usury/riba if the implementation is done based on the provisions of Islam.Sharia bank in its financing is required to apply sharia principles based on fatwa issued by the institution that having authority in determining fatwa in sharia and also required to conduct feasibility assessment to its costumer so that there is strong belief about willingness and ability of the prospective costumer to receive financing facility.Keywords: Sharia Bank, Murabahah, Justice